Managing People Costs in the Era of Talent Scarcity and Hybrid Work - Devina Agustin; Didik Heri Purnomo; Muhammad Zailiansyah Gumay; Yusnaini Yusnaini (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study was motivated by the increasing difficulty in securing skilled human resources (HR) in the post-pandemic era, which has led to rising labor costs and a shift toward hybrid work models. The objective of this study is to analyze the impact of talent scarcity on the structure and magnitude of HR costs and to identify optimal strategies for managing them through hybrid work. The method used is a systematic literature review of 15 relevant indexed scientific articles from the 2022–2025 period. The results indicate that talent scarcity drives increases in compensation costs, recruitment costs, and turnover risk, while hybrid work reduces fixed costs such as office infrastructure but increases variable costs such as technology and training. Furthermore, strategies such as determining the appropriate hybrid work ratio, organizational support, and adaptive leadership have proven effective in controlling HR costs. This study concludes that managing HR costs in the hybrid era requires a balanced and contextual strategic approach.